The impact of corporate social responsibility on firm efficiency - Trinh, Linh Tuan Doan; Nguyen, Uyen Phuong Le (Asian Journal of Economic Modelling, 2025)
The impact of corporate social responsibility (CSR) on business performance is increasingly becoming a topic of interest among scholars. This study examines how CSR influences the performance of sustainable businesses in Vietnam from 2019 to 2023. Business performance is measured through technical efficiency, calculated using the Data Envelopment Analysis (DEA) method. To analyze the relationship between CSR and business performance, the Tobit regression model is applied. The results indicate that CSR positively affects business performance when companies focus on economic and legal responsibilities, as these factors contribute to financial stability and regulatory compliance. However, ethical and philanthropic responsibilities tend to reduce operational efficiency, potentially due to increased costs or challenges in resource allocation. This suggests that while fulfilling economic and legal obligations enhances performance, businesses may face difficulties in balancing efficiency with ethical and philanthropic commitments. These findings highlight the need for strategic implementation of CSR to maximize both social impact and business efficiency. Companies should focus on optimizing ethical and philanthropic initiatives to minimize potential negative impacts while leveraging economic and legal responsibilities to drive performance. A balanced approach to CSR can contribute to both corporate sustainability and long-term operational effectiveness.